Effect of Bio-fertilizer, organic manure, Nano Zinc Oxid and interaction on the growth parameters for Sunflower plant Helianthus annuus L. - Al Myali, Ali Ahmed Hussein; Alnuaimi, Jassim Jawad Jader; Hussain, Madeha H. (Journal of Kerbala for Agricultural Sciences, 2020)
This study was conducted in the east part of karbala in Iraq , in order to deterrnine the effect of bio-fertilizer , levels of organic manure and nanozinc oxide on the traits , the number of days fom planting to 50% flowering , plant high , number of days form planting to maturation , leaf area , number of leaves , leaf chlorophyll content and disk diameter for sunflower . the split-split plots were used according to the randomized complete Block Design (RCBD) with three replicates . where the treatments of nanoZnO control and nanoZnO occupied the main plots , while the organic manure control ( 50 , 150 , 300 Kg.ha-1) NPK , the poultry manure 15 ton.ha-1 . the sheep manure 15 ton ha-1 and 1/2 amount of poultry manure and 1/2 amount the sheep manure occupied sub plots , while the bio-fertilization treatments ( 0 , mychorriza , Azospirillum and 1/2 amount mychorriza and 1/2 amount Azospirillum ) were occupied sub-sub- plots . The results showed the following the superiority of bio-fertilizer significantly in the traits of the number of days fom planting to 50% flowering , plant high , number of days form planting to maturation , leaf area , number of leaves , leaf chlorophyll content and disk diameter , the treatment mychorriza (C1) was excelled by giving in the lowest average for number number days for 50% flowering recorded 72.1 and 60.0 days for both season respectively and number days to maturation the plants treated with the michoriza recorded 101.6 days for spring season and the plants treated with Azospirillum recorded 91.7 days for autumn , while the plants of control treatment (C0) gave the highest average of 50 % flowering and maturation period . while the plants treated with the mychorriza + Azospirillum was excelled by giving the highest average for plant hight recorded ( 171.1 , 141.1) cm for two seasons respectively and highest average of leaf area recorded ( 8927 cm2 for autumn season the plant treated with the mychorriza was excelled giving the leaf chlorophyll content and highest average number of leaves the highest average recorder ( 50.5 , 52.43) spad and ( 15.37 , 17.9 ) leaf . The plant were treated with the (B1) was excelled by giving the best average recorded (69.7 , 59.9) days , ( 176.8 , 144.3) cm , (8426 , 11640) cm2 , (52.46 , 54.46 ) spad and ( 16.9 , 19.21) leaf for the treat flowering beard , plant high , leaf area , leaf chlorophyll content and number of leaves foe both season respectively , but the plant treated with the B2 was excelled by giving the lowest average of the maturation period recorded ( 99 , 98.88 ) days for both season respectively . The plant treated with the nano ZnO was excelled by giving in the lowest average of flowering and maturation period|. While was excelled by giving in the highest average of plant high , leaf area , leaf chlorophyll content , number of leaves of plant and disk diameter recorded ( 72.8 , 58.9) days , ( 103 , 89.95) days , ( 168.1 , 144.1) cm , ( 6259 , 8682) cm2 , ( 50.1 , 52.35) spad , ( 15.9 , 17.82) leaf and ( 17.6 , 22.67) cm for two season respectively. As will as bi and triple interaction was significantly affected on some trades in the both on alone of season.